Intensity Distribution and Neotectonic Macrostructure Pyrgos Earthquake Data (26 March 1993, Greece) - Lekkas, E.; Fountoulis, I.; Papanikolaou, D. (Natural Hazards, 2000)
We present a number of data for the Pyrgos (W.Peloponnessos, Greece), which took place on 26 March1993 and caused considerable damage in the town ofPyrgos and the surrounding area. The local geologicaland neotectonic conditions are also outlined; they aremainly characterized by complex stratigraphicstructure and outcrop pattern, together with a largenumber of large active fault zones and/or isolatedfaults. The detailed damage recording in themeizoseismal area, which was based on the EMS-92,showed significant differentiation of damage from oneurban unit to another, regardless of the foundationformation. The correlation of the existing dataconfirmed the decisive impact of faults and fault zoneon intensity distributions. It was also clear that,the larger a fault zone, the greater was thedifference in intensity across that structure.
10.1023/A:1008153620842